“Daños de Bactericera cockerelli en el cultivo de papa (Solanum tuberosum)”, en el barrio Eloy Alfaro, Parroquia La Libertad” - Paspuezán Calderón, Marcelo Aníbal (2019)
SUMMARY This work was carried out in the parish La Libertad whose theme was "Damages of Bactericera cockerelli in the cultivation of potatoes (Solanum tuberosum)", in the neighborhood Eloy Alfaro, Parroquia La Libertad ", began by an introduction that goes a bit into the origins and history of the dangers of the appearance of this insect in crops, the introduction of general knowledge at the level of the continent and ends with the current situation of the country with the control of this agent and the disease caused by it, objectives are set so that important conditions are attainable, measurable and reasonable so that the research does not get out of hand and is aimed at achieving them effectively. In Chapter II of the theoretical framework, it is aimed at obtaining a deeper understanding of the paratrioza pathogen (Bactericera cockerelli) but at the same time in a summary way in its main concepts, the transmitting agent responsible for the phytoplasma or purple tip is briefly mentioned that so much damage has caused worldwide, we also mention the potato and its cultivation, as well as the damage caused by this insect. Chapter III refers to the material resources that were used throughout the investigation, as well as the methodology and techniques to be used for the treatment of the information collected. Chapter IV presented the results obtained and the fulfillment of the objectives set. Chapter V consists of a series of conclusions and recommendations made by the author to solve the problem caused by the pathogen under investigation. With the above, the work presented has truthful and accurate information that makes it an excellent source of consultation. Keywords: paratrioza, purple tip, agent, pathogen, insect, potato, crop, chemicals, phytoplasma, targets, vector.